Synchronous tumors: clear cell carcinoma of pancreas and gastrointestinal stromal tumor of stomach (Annals of Medical Research, 2021)
None
Keywords: Pancreas Adenocarcinoma; Clear Cell Carcinoma of Pancreas; Gastrointestinal Stromal Tumor.